2015
DOI: 10.1111/acem.12765
|View full text |Cite
|
Sign up to set email alerts
|

Early Secondary Neurologic Deterioration After Blunt Spinal Trauma: A Review of the Literature

Abstract: Objectives: The objectives were to review published reports of secondary neurologic deterioration in the early stages of care after blunt spinal trauma and describe its nature, context, and associated risk factors. Methods:The authors searched the MEDLINE, EMBASE, and CINAHL databases for English-language studies. Cases were included meeting the criteria age 16 years or older, nonpenetrating trauma, and experiencing neurologic deterioration during prehospital or emergency department (ED) care prior to definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 102 publications
(149 reference statements)
0
9
0
Order By: Relevance
“…A recent systematic review did not reveal any evidence of neurological harm caused by any type of lateral positioning, including the log-roll maneuver [33]. This result was confirmed by Oto et al [34], who also concluded that "early secondary neurological deteriorations after blunt spinal trauma are exceptionally rare." Although a lack of evidence does not necessarily demonstrate the absence of harm, it seems reasonable that the motion induced by the log-roll maneuver could be used as a base for comparison for other lateral positioning techniques.…”
Section: Discussionmentioning
confidence: 85%
“…A recent systematic review did not reveal any evidence of neurological harm caused by any type of lateral positioning, including the log-roll maneuver [33]. This result was confirmed by Oto et al [34], who also concluded that "early secondary neurological deteriorations after blunt spinal trauma are exceptionally rare." Although a lack of evidence does not necessarily demonstrate the absence of harm, it seems reasonable that the motion induced by the log-roll maneuver could be used as a base for comparison for other lateral positioning techniques.…”
Section: Discussionmentioning
confidence: 85%
“…While unstable cervical spine injuries occur in 1% to 2% of trauma patients, cord injury occurs in only 0.1% to 0.4% 33,34 . Most spinal cord injury is sustained during the initial insult, and evidence suggests that secondary cord injury more frequently results from ischemia, edema, or iatrogenic manipulation rather than movement during extrication and transport 4,5,35 . Selective immobilization approaches based on National Emergency X-radiography Utilization Study criteria 36 and the Canadian C-Spine rules 37 aim to minimize harm from unnecessary immobilization while maintaining safety for patients at risk for secondary injury.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 However, the scientific basis for universal immobilization has never been well established. 4 Several studies have demonstrated an absence of benefit from prehospital immobilization, including a Cochrane review, which concluded that the practice is rooted in tradition rather than science. [5][6][7][8][9] Immobilization is, however, associated with significant risks, including aspiration and impaired airway management, 10,11 pulmonary restriction, 12 obscurement of critical examination findings, 13 increased intracranial pressure, 14,15 scene delays, 16 pressure injury, 17 pain, 18 and false-positive spinal tenderness leading to increased imaging use.…”
mentioning
confidence: 99%
“…Evidence of early secondary deterioration from spinal injuries is very rare and records of sudden deterioration following sudden movement are not very readily available [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%